2016
DOI: 10.1111/imr.12445
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted effects of Francisella tularensis on human neutrophil function and lifespan

Abstract: Summary Francisella tularensis in an intracellular bacterial pathogen that causes a potentially lethal disease called tularemia. Studies performed nearly 100 years ago revealed that neutrophil accumulation in infected tissues correlates directly with the extent of necrotic damage during F. tularensis infection. However, the dynamics and details of bacteria-neutrophil interactions have only recently been studied in detail. Herein we review current understanding regarding the mechanisms that recruit neutrophils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 165 publications
(330 reference statements)
0
58
0
Order By: Relevance
“…Francisella tularensis is a Gram‐negative, facultative intracellular bacterium and the causative agent of zoonosis tularaemia. Infection can ensue following inhalation of bacteria into the lungs, ingestion of contaminated food or water, direct contact with an infected animal carcass, or inoculation into the skin via the bite of an infected arthropod vector (Kinkead & Allen, ). As few as 10 organisms can result in severe disease with mortality rates up to 60% in untreated infections (Dennis et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Francisella tularensis is a Gram‐negative, facultative intracellular bacterium and the causative agent of zoonosis tularaemia. Infection can ensue following inhalation of bacteria into the lungs, ingestion of contaminated food or water, direct contact with an infected animal carcass, or inoculation into the skin via the bite of an infected arthropod vector (Kinkead & Allen, ). As few as 10 organisms can result in severe disease with mortality rates up to 60% in untreated infections (Dennis et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As few as 10 organisms can result in severe disease with mortality rates up to 60% in untreated infections (Dennis et al, ). F. tularensis subspecies tularensis (Type A) is exclusive to North America, whereas F. tularensis subspecies holarctica (Type B) is found throughout the northern hemisphere (Kinkead & Allen, ). Both Type A and Type B strains of F. tularensis replicate in phagocytes at sites of infection and disseminate to distal organs, including liver, spleen, and lymph nodes, leading to tissue destruction that may progress to sepsis or death, often prior to development of an adaptive immune response (Dennis et al, ; Kinkead & Allen, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After engulfment by phagocytic cells, Francisella transiently resides in a phagosomal compartment (Figure 1) that sequentially displays membrane markers of early (EEA1) and late endosomes/lysosomes (LAMP-1 and -2) but does not acquire the hydrolase cathepsin D or lysosomal tracers (Celli and Zahrt, 2013). Within the phagosome, Francisella must fight against several host antimicrobial defenses, including notably reactive oxygen species (ROS) produced by the NADPH oxidase (Kinkead and Allen, 2016). For this, Francisella is equipped with a series of enzymes that include superoxide dismutase, catalase and acid phosphatases (Jones et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Kinkead and Allen review studies from the Allen lab that have identified several maneuvers which Francisella employs to thwart neutrophil‐mediated killing and disturb neutrophil cell death pathways. Francisella not only survives within neutrophils but also globally interferes with oxidase activation .…”
mentioning
confidence: 99%